Editor's Introduction. Issue 1 (1st August 2021) - Kowalsky, Sharon A
Abstract : When Peter Hallama approached the Aspasia editorial board about publishing the proceedings of a conference he was organizing on Socialist Masculinities, we jumped at the opportunity. It seemed that Aspasia, as a journal of women's and gender history, would be the perfect venue to showcase the innovative and important historical scholarship being conducted on masculinities in Central, Eastern, and Southeastern Europe. Although the COVID-19 pandemic delayed his plans and necessitated holding a virtual conference, the results that make up the contents of this volume do not disappoint. As Hallama mentions in his Introduction to the Special Forum articles, and as Marko Dumančić highlights in his concluding Comments, the works included here reflect a deep engagement with the lived experiences of men, assessed through memoirs, diaries, photographs, newspapers, and internal party documents. These articles explore some of the many and shifting masculinities constructed throughout the region during the socialist period, showing that individuals and the state constantly engaged in their negotiation and renegotiation.